Diffuse Large B Cell Lymphoma in Wiskott-Aldrich Syndrome: A Case Report and Review of Literature - Senapati, Jayastu (Springer India, 2014)
Wiskott-Aldrich syndrome (WAS) is an X linked rare primary immunodeficiency syndrome with an increased propensity for infection, autoimmunity and malignancy. Here we report a male child, who was diagnosed with WAS at 1 year of age following evaluation for symptomatic thrombocytopenia and eczematous skin lesions. He presented later with lymphadenopathy, which was consistent with diffuse large B cell lymphoma on histopathology. He received 6 cycles of R-CHOP chemotherapy for the same and is presently in remission after 6 months. We review the major publications of lymphoma in WAS and discuss the pathological findings, treatment and prognosis of lymphoma in WAS.